Regulation of Cholesterol Binding to the Receptor Patched1 by its interactions With the Ligand Sonic Hedgehog (Shh) - Zhong, Changqing; Wang, Beibei (Frontiers in Molecular Biosciences, 2022)
The Hedgehog (Hh) signaling pathway is essential in cell development and regeneration, which is activated by the ligand Sonic hedgehog (Shh). The binding of Shh to its receptor Patched1 (PTCH1) releases the inhibitory effect on the downstream protein Smoothened (SMO), a G-protein-coupled-receptor (GPCR) protein. Cholesterol was supposed to function as a secondary messenger between PTCH1 and SMO. However, the molecular mechanism of this regulation process is still unclear. Therefore, microsecond coarse-grained molecular dynamics simulations were performed to investigate the protein-lipid interactions of the PTCH1 monomer and dimer-Shh complex. It was observed that the binding of cholesterols to the monomer is more stable than that to the dimer-Shh complex. It is regulated by the enrichment of Ganglioside lipids around proteins and the conformation of Y446, a residue in the sterol-sensing domain (SSD). The regulation of Shh on the dynamics of PTCH1 was further analyzed to explore the allosteric communication pathways between the Shh and the SSD. Our study provides structural and dynamic details of an additional perspective on the regulation of Hh signaling pathway through the lipid micro-environments of PTCH1.